Workplace fun for better team performance: focus on frontline hotel employees. Issue 7 (11th July 2016) - Han, Heesup; Kim, Wansoo; Jeong, Chul
Abstract : Purpose: The aim of this study is to reveal how workplace fun promotes team performance in the hotel business context. Design/methodology/approach: The conceptual model of this study was tested based on responses from 271 frontline hotel employees (including managers) in the USA, who had full-time work tenure of more than three months in a three-star or above-rated hotel. Findings: This study revealed that workplace fun activities enhance team performance by promoting employees' workplace fun experience and by facilitating interpersonal trust and group cohesion, which, in turn, reduce intra-group conflict and stimulates interpersonal citizenship behaviors, respectively. Research limitations/implications: First, this study adopted subjective team performance measures. Although it can be exaggerated unconsciously, the literature suggests that how team members perceive their team' performance is also an important indicator of team effectiveness. Second, the conceptual model of this study was tested in the US context. So, in a more collectivistic culture, the model might generate somewhat different results from those of this study. Practical implications: The findings of this study indicate that workplace fun initiatives by the management are an effective means to promote the performance of frontline work teams at a hotel. Discussions are extended to incorporating fun elements into existing organizational cultures. Originality/value: By adopting the input–process–outcome framework, this study shows how workplace fun, as a critical input, creates positive group processes and, thereby, promotes positive group outcomes in the hotel business context.